TUBERCULOUS GRANULOMA ON BONE MARROW TREPHINE - Karim, Farheen; Qadir, Hira (Journal of Ayub Medical College Abbottabad, 2019)
Bone marrow examination is a useful tool for diagnosis of many diseases. The utility of bone marrow examination in workup of pyrexia of unknown origin cannot be undermined. Bone trephine of patients presenting with pyrexia of unknown origin must carefully be looked upon for granulomas for evaluation of tuberculosis. In this case, bone marrow trephine aided in timely diagnosis of tuberculosis in a patient. Keywords: Bone trephine; Granulomas; Tuberculosis; Bone marrow